Network pharmacology-based analysis of potential mechanisms of myocardial ischemia-reperfusion injury by total salvianolic acid injection - Nan Li; Xufang Gu; Fanqi Liu; Yao Zhang; Yanjun Sun; Shengwei Gao; Baohe Wang; Chen Zhang (Frontiers Media S.A., 2023)
In this review, we investigated the potential mechanism of Total Salvianolic Acid Injection (TSI) in protecting against myocardial ischemia reperfusion injury (MI/RI). To achieve this, we predicted the component targets of TSI using Pharmmapper and identified the disease targets of MI/RI through GeneCards, DisGenNET, and OMIM databases. We constructed protein-protein interaction networks by analyzing the overlapping targets and performed functional enrichment analyses using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes. Our analysis yielded 90 targets, which were implicated in the potential therapeutic effects of TSI on MI/RI. Seven critical signaling pathways significantly contributed to TSI's protective effects, namely, PI3K signaling, JAK-STAT signaling, Calcium signaling, HIF-1 signaling, Nuclear receptor signaling, Cell Cycle, and Apoptosis. Subsequently, we conducted a comprehensive literature review of these seven key signaling pathways to gain further insights into their role in the TSI-mediated treatment of MI/RI. By establishing these connections, our study lays a solid foundation for future research endeavours to elucidate the molecular mechanisms through which TSI exerts its beneficial effects on MI/RI.